EFEKTIFITAS PELATIHAN TERHADAP KEPUASAN KERJA DAN KOMITMEN ORGANISASIONAL SERTA KINERJA KARYAWAN BANK - Fauzan, Rizky (Jurnal Keuangan dan Perbankan, 2015)
This research aimed to find out and to analyze the influence of training effectiveness to job satisfaction andorganizational commitment and employee performance. This research was a survey, which used explanatoryresearch. The population was 606 employees, and 127 of them were the permanent employees at PT.BankKalbar Pontianak. The research samples were 62 people. They were the employees in bachelor degree. Data wascollected using questionnaires, interviews and document study. Each item was measured by the reliability andvalidity of the study. Hypothesis testing was done by using path analysis. Based on the results of pathanalysis, it was found that: the effectiveness of the training significantly influenced the employee satisfaction,the effectiveness of the training significantly influenced organizational commitment, effectiveness of the trainingdid not have any significant effect on the performance of employees, job satisfaction significantly influencedthe organizational commitment, job satisfaction significantly affected the performance of employees,organizational commitment significantly influenced the employees performance.